Strengthening the Position of Child Victims as Witnesses Through Video Recordings in Sexual Violence Crimes (A Comparison Between Indonesia and Malaysia) - Aprilianda, Nurini; Kadir, Nadhilah A.; Bagaskoro, Ladito Risang; Yuliani, Anggi Ari (Brawijaya Law Journal, 2024)
The increasing number of children as witnesses in proving a criminal offense presents a problem in the Indonesian criminal justice system. Based on Article 184 of the Criminal Procedure Code, evidence provided by witnesses must meet specific requirements, including being given by adults. Consequently, testimony from child witnesses is not recognized as valid evidence, as they are not sworn in and are considered legally immature. Apart from that, the impact of technological developments, such as the use of video to record children's statements as witnesses, has not yet become part of witness statements as a valid form of evidence. However, the Malaysian legal system, through the Evidence of Child Witness Act 2007, has made legal breakthroughs that allow child victim statements as admissible evidence through recorded footage, live video, and in-person testimony. This research seeks to reinforce the role of children as witnesses by employing a normative juridical method, along with statutory and comparative legal approaches, to explore potential changes in legislation to incorporate video-recorded testimony for child witnesses. Legislative updates may involve revising (a) the Child Protection Law; (b) the Criminal Procedure Code (KUHAP); and (c) the Electronic Information and Transactions Law. Besides, practical steps could support these changes, such as creating dedicated spaces with appropriate technology, establishing protocols and standards for child witness testimonies, and providing specialized training for judges, prosecutors, and investigators.